Fun Ways in Learning English - Nurul An-nisa; Tono Suwartono (Journal of Applied Linguistics (ALTICS), 2020)
To some, learning English appears to be complicated. In the academic contexts, students still get difficulties in learning English. Teachers as educatorsshould be creative in choosing the best method to teach the language. Learning strategies that are less fun or arguably boring do not improve students’ English skills, instead will only make students feel bored and lazy to learn. The most important thing is that students enjoy every learning process as something fun. It can help the students feel comfortable during the learning process. Fun learning activities will have an impact on improving students’ English abilities naturally. It helps students to reduce pressure during learning. Therefore, the ways of learning must be designed and adapted to the needs of students. This paper is non-research based. It means that the paper is about author’s perspective of how to learn English in fun ways. This article enlists several fun ways in learning English. So, the students can find their enjoyment in learning English.Keywords: Fun, Learning English, Strategies, Method